Pengembangan User Interface Sistem Informasi Planned Maintenance System pada PT. Pertamina Trans Kontinental dengan Menggunakan Metode Design Sprint - Pribadi, Jelang Romadhon Kharismawan; Sagirani, Tri; Kartikasari, Puspita (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2019)
PT. Pertamina Trans Kontinental (PTK) is company that active in a maritime logistics, therefore its vessels idle time during maintenance become a crucial aspects for PTK because it affect their core business activity directly. To support every maintenance agenda, PTK develop a computerized maintenance management system (Planned Maintenance System) that help maintaining every detail of the vessels. In its implementation, User Interface Design is an important aspect since UI bridge the interaction between human and the system built. A system implementation without considering interaction between user and the system will result in a difficult interaction between user and the system. By evaluating user interface’s usability, It’s expected that the UI recommendations will be developed in accordance with the problems faced by the users. The evaluation is held before and after the design process which use Design Sprint Method. The proposed design final evaluation conclude that there was a 24.13% increase in score, leveraging the average score from 2.50 to 3.29.